2018
DOI: 10.1590/1677-5449.003817
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with outcome of endovascular treatment of iliac occlusive disease: a single-center experience

Abstract: Background Endovascular treatment (ET) of iliac occlusive disease (IOD) is well established in literature. Use of stents in IOD has achieved long-term limb salvage and patency rates similar to those of open surgery, with lower morbidity and mortality rates. Objectives To report the long-term outcomes, particularly limb salvage and patency rates, of ET for IOD and the factors associated with these outcomes. Methods This retrospective cohort study included patients with IOD who underwent iliac angioplasty (IA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Notably, these mortality rates were lower compared to those reported in related studies. Specifically, studies by Kasemi et al and Soares et al, which both examined the outcomes of iliac artery interventions, reported higher mortality rates of 4.5% and 4.3% respectively ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these mortality rates were lower compared to those reported in related studies. Specifically, studies by Kasemi et al and Soares et al, which both examined the outcomes of iliac artery interventions, reported higher mortality rates of 4.5% and 4.3% respectively ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…aorta + CIA, p = 0.16). Similarly, Soares et al [25] compared the outcomes between CIA and EIA vs . CIA, and they found that the primary patency rates were similar between the patient’s groups.…”
Section: Discussionmentioning
confidence: 99%